(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can infect the kidney and the presence of chronic kidney disease (CKD) constitutes a higher risk of negative prognosis. SARS-CoV-2 main sequelae in CKD patients are an incomplete recovery of kidney function, muscle weakness and atrophy, breathiness, tiredness, pulmonary fibrosis, and initiation of kidney replacement therapy. The overall aim of this review is to provide a theoretical basis for early improvements of physical function health to all CKD stages by rehabilitation therapies.